Evaluasi Kepatuhan Standar Hukum dalam Layanan Pengangkutan Barang di Indah Logistik Cargo Kota Malang - Friska Aprilia Pramesti; Anis Shilvi Rahmawati (Sharia Faculty of Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2026)
The logistics industry in Indonesia has experienced rapid growth in response to the increasing demand for fast and efficient delivery services. However, this development also brings challenges in regulatory compliance, particularly concerning consumer protection and transportation safety. This study aims to evaluate the implementation of legal standards in freight transportation services at Indah Logistic Cargo in Malang City, focusing on compliance with Law No. 8 of 1999 on Consumer Protection and Law No. 22 of 2009 on Road Traffic and Transportation. The research employs an empirical juridical method, with data collected through observations and interviews with company management and consumers. The findings reveal that the company has implemented some legal provisions, such as compensation claim mechanisms and vehicle inspections, but several issues persist, including discrepancies in item weight, damage to fragile goods, and delivery delays. Such inconsistencies may violate consumer rights as stipulated in Article 8 of the Consumer Protection Law. Moreover, the company’s administrative compliance remains incomplete, particularly regarding the Company Registration Certificate (TDP). Therefore, improvements are needed in employee training on legal regulations, the adoption of technology-based logistics management systems, warehouse infrastructure upgrades, and the development of a more responsive complaint-handling mechanism. Strengthening legal, operational, and service aspects will help Indah Logistic Cargo enhance regulatory compliance, customer satisfaction, and competitiveness in Indonesia’s logistics industry.